Morphological and genetic identification of formalin-fixed gobioid larvae and description of postflexion larvae of Paragunnellichthys sp. and Ctenogobiops feroculus - Hanahara, Nozomi; Miyamoto, Kei; Oka, Shin-ichiro (Ichthyological Research, 2021)
Gobioid larvae collected from the coast of Okinawa Island, southern Japan, were identified on the basis of a combination of morphological characters and a sequence of a hypervariable region of mitochondrial 12S ribosomal RNA (12S rRNA) gene (138–145 base pairs). A short-term formalin fixation technique enabled identification using both morphological and genetic methods. Thirteen of the 21 types of gobioid larvae assessed were identified to the species level. Additionally, we described the morphology of the postflexion larvae of wormfish Paragunnellichthys sp. and shrimp-associated goby Ctenogobiops feroculus , identified for the first time in their respective genera.